Development of a New High-Cell Density Fermentation Strategy for Enhanced Production of a Fungus β-Glucosidase in Pichia pastoris - Liu, Wancang; Xiang, Haibo; Zhang, Tao; Pang, Xu; Su, Jing; Liu, Hongyu; Ma, Baiping; Yu, Liyan (Frontiers in Microbiology, 2020)
Traditional diosgenin manufacturing process has led to serious environmental contamination and wastewater. Clean processes are needed that can alternate the diosgenin production. The β-glucosidase FBG1, cloned from Fusarium sp. CPCC 400709, can biotransform trillin and produce diosgenin. In this study, Pichia pastoris production of recombinant FBG1 was implemented to investigate various conventional methanol induction strategies, mainly including DO-stat (constant induction DO), μ-stat (constant exponential feeding rate) and m-stat (constant methanol concentration). The new co-stat strategy combining μ-stat and m-stat strategies was then developed for enhanced FBG1 production during fed-batch high-cell density fermentation on methanol. The fermentation process was characterized with respect to cell growth, methanol consumption, FBG1 production and methanol metabolism. It was found that large amounts of formaldehyde were released by the enhanced dissimilation pathway when the co-stat strategy was implemented, and therefore the energy generation was enhanced because of improved methanol metabolism. Using co-stat feeding, the highest volumetric activity reached ~89  104 U/L, with the maximum specific activity of ~90  102 U/g. After 108 h induction, the highest volumetric production reached ~403 mg/L, which was ~91, 154, and 183 mg/L higher than the maximal production obtained at m-stat, μ-stat, and DO-stat strategies, respectively. FBG1 is the first P. pastoris produced recombinant enzyme for diosgenin production through the biotransformation of trillin. Moreover, this newly developed co-stat induction strategy represents the highest expression of FBG1 in P. pastoris, and the strategy can be used to produce FBG1 from similar Pichia strains harboring Fbg1 gene, which lays solid foundation for clean and sustainable production of diosgenin. The current work provides unique information on cell growth, substrate metabolism and protein biosynthesis for enhanced β-glucosidase production using a P. pastoris strain under controlled fermentation conditions. This information may be applicable for expression of similar proteins from P. pastoris strains.